If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = r + -19 Reorder the terms: -2 = -19 + r Solving -2 = -19 + r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1r' to each side of the equation. -2 + -1r = -19 + r + -1r Combine like terms: r + -1r = 0 -2 + -1r = -19 + 0 -2 + -1r = -19 Add '2' to each side of the equation. -2 + 2 + -1r = -19 + 2 Combine like terms: -2 + 2 = 0 0 + -1r = -19 + 2 -1r = -19 + 2 Combine like terms: -19 + 2 = -17 -1r = -17 Divide each side by '-1'. r = 17 Simplifying r = 17
| 3(3t-4)-(t^2+5)-4t(t-3)=0 | | 8/7=k/8 | | M(m-10)=0 | | 6b+9=-4b+28 | | (-8)/(x+6)=-5 | | 5/(n-12)=-1/n | | 4z^2-16z+12=0 | | x^2(x^2+3x+2)= | | 3y+2.5x-3.7=0 | | x=-22+-6w | | -110=2(1+8) | | 2y^2=-y+10 | | 4-5k-6=-4k-1 | | (6/7)x=24 | | 7x+4=5x-1 | | 2=f/2 | | -182=-6(7-6n)-n | | 4z^2-16+12=0 | | 7x+3/2-9x-8/4=6 | | -22-x=3w-w+4w | | 4/5x+4/3+2x | | 1/5x-y=76 | | -7p-(-7+5p)=-4(3p-7) | | 5(1+7)-5=175 | | x+4/15=-1 | | (7x^2-7x+8)+(9x^3-5x)= | | 3(x+3)+12=6x+3 | | 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 |